THE PSYCHOLOGICAL CHARACTERISTICS OF SOCIAL NEUROTICISM - Petrosyan, Rafik (Modern Psychology, 2025)
Research of neuroticism nowadays increasingly touches upon the social aspect of psychological sciences. The level of expression of neuroticism affects not only a person’s well-being but also has a certain influence on an individual’s self-esteem, ability to freely communicate, and self-realization in society. In this article the problem of neuroticism is considered from the social-psychological point of view, special attention is paid to the manifestation of social neuroticism among immigrants, with special importance on research on social neuroticism in conditions of change of social environment and adaptation to new social conditions is emphasized. It was found that among immigrants, the level of neuroticism correlates with the level of satisfaction with the profession and has certain gender differences in the intensity of correlations. Negative correlations were found between the degree of professional satisfaction and low self-esteem in the group of men (-799**), depression in the groups of men (-869**) and women (-797***). The practical significance of the work also lies in the social significance of the study, the results of which can be supplemented by studies on the characteristics and manifestation of social neuroticism among various age groups of immigrants and other social groups in society.